HUBUNGAN ANTARA ASAS KEBEBASAN BERKONTRAK, PACTA SUNT SERVANDA, DAN ITIKAD BAIK - Hudaningrum, Fitria (REPERTORIUM, 2014)
AbstractRecognized the various principles of contract law governing the agreement. The principles include the principle of freedom of contract, the principle of consensualism, pacta sunt servanda, and the principles of good faith. In thin case, will be assessed on relationship between the freedom of contract, pacta sunt servanda, and good faith. Agreement ia a requirement for two people the basis of the principles of good faith to accept agreement that the covenant they made a law for them to be implemented.AbstrakHukum kontrak mengenal berbagai asas yang mengatur suatu perjanjian. Asas tersebut meliputi asas kebebasan berkontrak, asas konsensuil, asas pacta sunt servanda, dan asas itikad baik. Dalam hal ini akan dikaji mengenai hubungan antara asas kebebasan berkontrak, asas pacta sunt servanda, dan asas itikad baik. Perjanjianmerupakan kehendak bagi dua orang atau dua pihak yang dilandasi dengan itikad baik untuk membuat suatu perjanjian sehingga perjanjian yang mereka buat merupakan undang-undang bagi mereka untuk dilaksanakan.